2005
DOI: 10.1111/j.1399-5618.2005.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life for patients with bipolar disorder: relationship with clinical and demographic variables

Abstract: Bipolar patients experience lower functioning and well-being even in the stable phase of the disorder. Due to the great impact of bipolar disorder on many areas, it would be of interest to know the clinical predictors related to patient quality of life, as this would contribute to the design of different clinical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
65
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 27 publications
(25 reference statements)
18
65
2
5
Order By: Relevance
“…74, Nineteen studies 74,97,98,[102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] contained data on the SF-36, one study involved the SF-12 101 and four studies [98][99][100][101] contained data on the EQ-5D. No studies were identified that examined the SF-6D in individuals diagnosed with bipolar disorder.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…74, Nineteen studies 74,97,98,[102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] contained data on the SF-36, one study involved the SF-12 101 and four studies [98][99][100][101] contained data on the EQ-5D. No studies were identified that examined the SF-6D in individuals diagnosed with bipolar disorder.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…Fourthly, we used randomization process so that we could assessed better result for the effect of provided care. 8 Finally, during the follow-up of the study, we were in telephonic contact with the patient so that we could control the attrition rate of the study. Besides these positive points, our study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…7 Due to cyclic nature of bipolar disorder symptom remission and symptomatic exacerbation can affect the patients' physical; psychological, emotional, economic and social well-being which is directly impaired their overall quality of life. 8 The usual treatment of bipolar disorder in here pharmacotherapy and psycho-education, many patient responses adequately for such kind of approach but some of do not. They may frequently suffer from the cyclic episode, cognitive impairment, and poor social well-being.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Bozukluğun düzelme ve alevlenmelerle seyreden döngüsel gidişi, bireyi fiziksel, duygusal açıdan etkilemekte, aile fonksiyonlarını, mesleksel ve sosyal açıdan uyumunu bozmaktadır. [2] Bununla birlikte hastaların sadece atak dönemlerinde değil, atak dışındaki dö-nemlerde de klinik olarak yaşam kalitelerinde belirgin bozulma olduğu belirtilmektedir. [3] Bipolar bozukluğu olan hastalar ve onlara bakım verenlerin birçok fonksiyonu hastalık sürecinde etkilenmektedir.…”
Section: Introductionunclassified